Use of Hydroxychloroquine And Risk of Heart Failure in Patients With Rheumatoid Arthritis - Sorour, Ahmed A. (J Rheumatol, 2021)
OBJECTIVES. To examine the relationship between the use of Hydroxychloroquine (HCQ) and risk of developing Heart Failure (HF) in Rheumatoid Arthritis (RA). METHODS. In this nested case-control study, cases were Olmsted county, Minnesota residents with incident RA (based on 1987 ACR criteria) from 1980-2013 who developed HF after RA incidence. Each case was matched on year of birth, sex and year of RA incidence with an RA control who did not develop HF. Data on HCQ use including start and stop dates and dose changes was reviewed, and used to calculate HCQ duration and cumulative dose. Age-adjusted logistic regression models were used to examine the association between HCQ and HF. RESULTS. The study identified 143 RA cases diagnosed with HF (mean age 65.8, 62% females) and 143 non-HF RA controls (mean age 64.5, 62% female). HCQ cumulative dose was not associated with HF (Odds Ratio [OR]: 0.96 per 100g increase in cumulative dose, 95% confidence interval [95% CI]: 0.90-1.03). Likewise, no association was found for patients with a cumulative dose ≥300g (OR 0.92, 95% CI 0.41-2.08). The HCQ duration of intake in years prior to index was not associated with HF (OR 0.98, 95% CI 0.91-1.05). CONCLUSIONS. Use of HCQ was not associated with development of HF in patients with RA in this study. Further studies are needed to understand the impact of higher doses of HCQ on development of HF in RA.